Prayer & Community : The Havurah in American Judaism - Prell, Riv-Ellen, 1947- (Book collections on Project MUSE., 2018)
Riv-Ellen Prell spent eighteen months of participant observation field research studying a countercultural havurah to determine why these groups emerged in the United States during the 1970s. In her book, she explores the central questions posed by the early havurot and their founders. She also examines the havurah as a development of American Judaism, continuing-rather than rejecting-many of the previous generations' ideas about religion. Combining history and ethnography, Prell uses current theories about ritual and prayer to understand men's and women's struggles with their religious tradition and their desire to create community.